Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor Dengan Kebijakan Penghapusan Denda Pajak dan Biaya Balik Nama Kendaraan Bermotor Berdasarkan Surat Keputusan Gubernur No 44 Tahun 2017 - Kurniawan, Pratomo Cahyo (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to discuss Taxpayer Compliance, Factors that can influence it, and Government Efforts to Motivate Taxpayers in relation to Regulation No. 44 of 2017. This research is used to obtain a comprehensive understanding of the essence of Taxpayer Compliance and Factors which affects the Taxpayer Compliance Level to increase provincial government revenues from PKB & BBNKB. This research is a qualitative research. Data obtained in this study were collected through direct observation in the field. The data analysis technique used is by conducting activities interactively. Data analysis in qualitative research was carried out at the time of data collection. The results of the study indicate that the level of tax compliance is very important in order to increase regional income. The government needs to improve services, make transparency, and improve facilities and infrastructure in paying taxes.Keywords: Taxes, Motivation, Increased Income, Public Services.